2016
DOI: 10.1200/jco.2016.34.4_suppl.493
|View full text |Cite
|
Sign up to set email alerts
|

MAVERICC, a phase 2 study of mFOLFOX6-bevacizumab (BV) vs FOLFIRI-BV with biomarker stratification as first-line (1L) chemotherapy (CT) in patients (pts) with metastatic colorectal cancer (mCRC).

Abstract: 493 Background: Standard 1L mCRC treatment (tx) includes a CT backbone (e.g., modified leucovorin [LV]/5-fluorouracil [5-FU]/oxaliplatin [mFOLFOX6] or LV/ 5-FU/ irinotecan [FOLFIRI]) and biologic therapy (e.g., BV). The preferred CT backbone for anti VEGF tx is unknown. MAVERICC (NCT01374425), a global, randomized, open-label, phase 2 trial, assessed tx efficacy and safety of mFOLFOX6-BV vs FOLFIRI-BV in pts with mCRC. Intratumoral ERCC1 and plasma VEGF-A were studied as biomarkers for oxaliplatin- and BV-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
2
14
0
1
Order By: Relevance
“…The relative dose intensity of 68.8 % for oxaliplatin was lower than that in the OPUS trial, with no apparent negative effect on efficacy. The median number of administered cycles of oxaliplatin in our study was 10, similar to the 11 cycles in the modified-FOLFOX6 arm of the recently reported MAVERICC study [16].…”
Section: Discussionsupporting
confidence: 56%
“…The relative dose intensity of 68.8 % for oxaliplatin was lower than that in the OPUS trial, with no apparent negative effect on efficacy. The median number of administered cycles of oxaliplatin in our study was 10, similar to the 11 cycles in the modified-FOLFOX6 arm of the recently reported MAVERICC study [16].…”
Section: Discussionsupporting
confidence: 56%
“…It has therefore been proposed as a surrogate biomarker for oxaliplatin resistance. However, clinical trials have not demonstrated the predictive ability of ERCC1 in oxaliplatin‐based treatment . Thus, EMSO has not recommended ERCC1 testing prior to the use of oxaliplatin in routine practice …”
Section: Chemotherapy Drugs For Precision Treatmentmentioning
confidence: 99%
“…KRAS status has also been evaluated as a prognostic biomarker. A recent analysis of the MAVERICC trial evaluated the prognostic role of KRAS (18). This phase 2 randomized clinical trial compared the combination of FOLFOX plus bevacizumab vs. FOLFIRI plus bevacizumab, with KRAS found to be a prognostic biomarker.…”
Section: Ras In Crcmentioning
confidence: 99%